Penatalaksanaan Holistik pada Lansia dengan Stroke Disertai Ulkus Dekubitus dan Hiperkolesterolemia Melalui Pendekatan Kedokteran Keluarga - Natasha Naomi Harli Putri; Diana Mayasari (Medula, 2020)
Stroke is the second leading cause of death and the third cause of disability in the world. Globally, 87% of strokes related to death and disability occur in low-medium income countries. Recovery from a stroke depends on many factors including the risk, the accuracy and speed of management, the disease that aggravates stroke and treatment and the implementation of early mobilization to prevent one complication of prolonged bed rest. Things to consider in handling post-stroke patients is family support. Family support can support patient recovery and recovery. The study conducted was a case report. Primary data was obtained through history taking and physical examination by making home visits. The assessment was carried out based on a qualitative initial holistic diagnosis, process, and end of visit. Based on the examination, the patient was a 62-year-old woman diagnosed with stroke, pressure sores, hypercholesterolemia, history of hypertension, and nucleus pulposus hernias. Very limited patient knowledge about the disease is evident from patients and family who have never been controlled or treated. Education and intervention are given to patients and families about stroke and its relationship with hypercholesterolemia and a history of hypertension, its complications in the form of pressure ulcers, hernia nucleus pulposus suffered by the patient and its treatment in 3 home visits. In the evaluation found an increase in patient compliance to avoid risk factors and family knowledge about patient care. Unhealthy lifestyles and lack of knowledge of patients about the disease become risk factors for the occurrence of disease in patients. Services with a family medicine approach in pharmacological and non-pharmacological therapy are able to solve health problems and improve the quality of life of patients.